THE IMPACT OF INDUSTRIAL REVOLUTION 4.0 AND ITS MANIFESTATION IN ISLAMIC FINANCE INDUSTRY - Syukqran Kamal; Rashid Ating; Arif Foenna (International Journal of Accounting, Finance and Business, 2020)
The advent of a new era, the Industrial Revolution (IR4.0) promotes the greater application of highly automated tools and innovation of cutting-edge technology which minimizes human intervention and it expedites normal processes in the current ecosystem in the banking industry. This paper attempts to explore the significance of IR4.0 in the Islamic finance and banking industry by analysing the nexus between IR4.0 and Islamic banking notably on financial technology (Fintech) adoption. The findings reveal that IR4.0 in the Islamic banking system is compatible with the current financial technology (Fintech) application such as blockchain, Robo-advisory, P2P financing, crowdfunding, and payment gateway. Nevertheless, it is not being fully utilized by most Islamic countries due to the financial and regulatory constraints and the lack of human capital in software development. The study also found that IR4.0 is highly developed and accepted in the European countries compared to the Islamic countries. Moving forward, more extensive studies and researches are needed on this subject to raise awareness to the industry players on the benefits and importance of IR4.0. This paper contributes to the dearth of literature on IR4.0 as the existing literature do not connect these two themes; Islamic banking and IR4.0